Evaluasi Kualitas Website Dengan Webqual Dan Importance-Performance Analysis (Studi Pada Website Perusahaan Daerah Air Minum Surya Sembada Surabaya) - Fajar Ramadhan Haikal; Admaja Dwi Herlambang; Niken Hendrakusma Wardani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Surya Sembada Regional water utility company Surabaya using website technology for customer to find bill information or water installation. Until this day surya sembada website has never been evaluated to check by web provider whether the website already fulfill user expectation or not. This research is using WebQual method that creates 3 main focus variable which is usability, information quality, and service interaction to assess site quality from user perspective. Then with Importance Performance Analysis (IPA) method to assess the quality of product and service based on customer perspective. The collection of data was obtained by distributing questionnaire to 100 respondents. The sampling technique used is convenience sampling. The data analysis technique using descriptive statistics. The result of this research is indicators from WebQual method that require recommendation based on quadrant IPA analysis in quadrant low priority. In variable usability indicators that require recommendations are easy to trace, draw, and design. In variable information quality there are no indicators that require recommendations. In service interaction variables indicators that require recommendations are good reputation, personalization, and community.